PENGARUH PERTUMBUHAN EKONOMI, INVESTASI, DAN UPAH MINIMUM TERHADAP TINGKAT PENGANGGURAN DI JAWA BARAT - Ramadhani, Qatrunnada Nisrina; Ananda, Candra Fajri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The objective of this study is to find out how the unemployment rate in each of West Java's districts and cities would change between 2018 and 2022 in relation to economic growth, investment, and minimum wages. Over a five-year period, a panel data collection comprising 27 districts and towns was utilized to accomplish this goal. Regression analysis with panel data was applied. The findings indicate that from 2018 to 2022, minimum wage, investment, and economic growth all had a considerable impact on the unemployment rate in all West Javan districts and cities. Economic growth holds a negative and significant effect on the unemployment rate, while investment has a negative and significant impact at 10% alpha on the unemployment rate. The minimum wage significantly and positively affects the unemployment rate. Investments made are mostly capital intensive and not yet equally distributed throughout West Java. Therefore, in order to lower unemployment, local governments are expected to increase labor-intensive investment.